An Algorithm for Ultrasonic Identification of Ceramic Materials and Virtual Prototype Realization - LIU, Yu; HE, Xiping; HE, Shengping (Archives of Acoustics, 2024)
To prevent important items from being replaced by a forgery, an ultrasonic fingerprint identification algorithm is proposed and an identification program is developed. A virtual prototype for the ultrasonic identification of ceramics is developed based on an ultrasonic detection card. This virtual prototype allows for the simultaneous transmission and acquisition of signals. Numerous experimental tests were conducted using this virtual prototype. The results demonstrate that the virtual prototype achieves accurate identification of ceramics. This virtual prototype lays a good foundation for the development of intelligent, automated, integrated, and miniaturized ultrasonic identification systems.